Phenotypic and morphometric characteristics of Bangkaew dog in Phitsanulok Province, Thailand - Suphawadee Yaemkong; PRAPASIRI JAIPONG; PATTHANUN KOTHAM; TUAN NGUYEN NGOC (Society for Indonesian Biodiversity, 2019)
Abstract. Yaemkong S, Jaipong P, Kotham P, Ngoc TN. 2019. Phenotypic and morphometric characteristics of Bangkaew dog in Phitsanulok Province, Thailand. Biodiversitas 20: 2877-2882. A research study was conducted to analyze phenotypic and morphometric characteristics of Bangkaew dogs in Mueang, Phromphirum, and Bangrakam districts, Phitsanulok Province, Thailand. In total, 54 Bangkaew dogs were randomly sampled by purposive sampling from 20 farmers between November 2018 and March 2019. The data consisted of nine phenotypic characteristics that were recorded visually and five morphometric characteristics that were obtained by using descriptive statistics and analysis of ANOVA to compare difference among means and correlation coefficients. Majority of the standard identities of Bangkaew dogs were according to the breed such as the guard coat around the face (100.00%), the guard coat around the neck or the chest coat (100.00%), the coat of belly (100.00%), the guard coat behind ears (100.00%), the lion’s leg shape (100.00%), the long coat from hip to the upper thigh (100.00%), and the plume tail (100.00%), except for the guard coat from the ruff around the shoulder (98.15%). Moreover, the coat of hair of Bangkaew dogs in this study was white-brown color (55.31%), followed by white-gray color (23.92%), white-black color (10.78%), brown color (6.44%), gray color (2.11%), and black color (1.44%), respectively. Least square means of males morphometric characteristics was significantly (p<0.05) greater than female body weight (21.44 ± 3.33 kg vs. 19.04 ± 3.01 kg), body height (49.52 ± 4.09 cm vs. 46.21 ± 5.30 cm) and leg length (38.64 ± 8.88 cm vs. 34.31 ± 5.75 cm), except for body width (19.48 ± 5.82 cm vs. 17.76 ± 4.24 cm; p>0.05), and for body length of females (55.76 ± 9.37 cm vs. 55.00 ± 7.18 cm; p>0.05) was superior to males of Bangkaew dogs. The correlations among morphometric characteristics such as body width vs. leg length, body length vs. body height, body weight vs. body height, body weight vs. body length, and body height vs. leg length, were 0.64, 0.56, 0.52, 0.34, and 0.33, respectively. These results implied that in order to conserve standard identities and improve morphometric characteristics, their typical characteristics such as structure, coat of hair and body size required by raisers should be considered in the breeding selection and mating system.